Strategi Menjadi Entrepreneur Kreatif di Era Digital - Isnaini, Dewi Budhiartini Juli; Nasti, Nilawati; Al Qohirie, Mohammad Irfan; Ernanda, Yovie; Sunaryo, Sunaryo; Ardiani, Winda (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The rapid development of digital technology has opened up significant opportunities for business actors, particularly MSMEs in the regions, to act as innovative and creative entrepreneurs. MSMEs, born and raised amidst technological advancements, have enormous potential to create digital-based businesses. However, to maximize this potential, they need to understand the opportunities available, the challenges they face, and the right strategies for entrepreneurship. This community service program aims to delve deeper into the characteristics of MSMEs that support entrepreneurship, explore business opportunities in the digital era, and provide strategic recommendations that can help this generation overcome challenges and capitalize on opportunities to succeed as entrepreneurs. Through a sound understanding of digital entrepreneurship, MSMEs can create businesses that are not only innovative and creative, but also sustainable and have a positive impact on society.